Outcomes of Combined Liver and Pancreas Transplantation: A Review of the SRTR National Database and a Report of the Largest Single Center Series - Li, Cheukfai; Zhang, Wei; Zhao, Qiang; Ye, Maodong; Ju, Weiqiang; Wu, Linwei; Ma, Yi; Hu, Anbin; Wang, Guodong; Zhu, Xiaofeng; Guo, Zhiyong; Wang, Dongping; et al. (Frontiers in Medicine, 2020)
Purposes: This study was intended to summarize the characteristics and clinical outcome of Liver and Pancreas (LPTx) recipients in the Scientific Registry of Transplant Recipients (SRTR) database versus the largest series from the First Affiliated Hospital (FAH), Sun Yat-sen University. Methods: The clinical data of 23 patients who underwent LPTx from 2000 to 2016 in the United States and 31 patients who underwent modified LPTx procedure (known as simplified multivisceral transplantation [SMT]) from 2008 to 2017 in our center were reviewed. The indications, surgical techniques, patient and graft survival, and complications were compared between the two groups. Results: All recipients in the FAH group were diagnosed with type 2 diabetes mellitus, while 10 of 23 recipients were diagnosed with type 1 diabetes mellitus in the SRTR group. The 1-, 3-, and 5-year cumulative patient survival rates were 81%, 74%, and 74% in the FAH group, respectively, and 51%, 47%, and 37% in the SRTR group, respectively (P=0.023). No diabetes was observed during follow-up in the FAH group, while the diabetes recurrence rate was 22.2% in the SRTR group (P=0.03). Conclusion: With multiple techniques modified and indications changed, the SMT procedure yielded a preferable outcome compared to that of the traditional LPTx procedure in records of SRTR. SMT has become a treatment option for patients with end-stage liver disease and concurrent diabetes.